If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + -2r = 2r + 4 Reorder the terms: -20 + -2r = 4 + 2r Solving -20 + -2r = 4 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. -20 + -2r + -2r = 4 + 2r + -2r Combine like terms: -2r + -2r = -4r -20 + -4r = 4 + 2r + -2r Combine like terms: 2r + -2r = 0 -20 + -4r = 4 + 0 -20 + -4r = 4 Add '20' to each side of the equation. -20 + 20 + -4r = 4 + 20 Combine like terms: -20 + 20 = 0 0 + -4r = 4 + 20 -4r = 4 + 20 Combine like terms: 4 + 20 = 24 -4r = 24 Divide each side by '-4'. r = -6 Simplifying r = -6
| =(16*16*16) | | 17-4x=19-5x | | 0.6+0.004+0.07+0.0098= | | 8x-5=-3x+20 | | 54-5x=13x+20 | | 2(12y+15)=y+(31-5y) | | 6x+10=98+5x | | 4-(12y+15)=y+(31-5y) | | 2x-130=16 | | 2.7q-3.4-5.6q=-3.9q-5.5 | | 5x^2+9=132 | | 3x-2(0)=6 | | 3x+10=4x-10 | | 3-2(0)=6 | | 5p+2=7+4p | | -43.-74= | | .2x+.6-x=-4(-.1+.1x) | | 76-2x=16x+16 | | 9y+26=5-6 | | 2(a+3)+3(a-2)= | | 14x+94=6 | | 2a+3+3a-1= | | 30v-100=626 | | (2x+5)(-3x+1)=19 | | 3(x+6)=5x+2 | | 2x+6-x=4-4x | | 12a+14=6s+20 | | 3(-3)-2y=6 | | 2x-8y=-86 | | (2x+5)-(-3x+1)=19 | | -2-3-4-5= | | 5=8y-9 |